2017
DOI: 10.1177/1073191117732411
|View full text |Cite
|
Sign up to set email alerts
|

Are Type, Frequency, and Daily Time Equally Valid Estimators of Support Needs in Children With Intellectual Disability? A Multitrait–Multimethod Analysis of the Supports Intensity Scale for Children (SIS-C)

Abstract: Support needs represent the intensity of support required by a person with a disability in order to take part in the activities related to normative human functioning. The Supports Intensity Scale for Children (SIS-C) is possibly the most promising tool for assessing and designing individualized support programs in children with intellectual disability. The SIS-C measures support needs across 61 activities, each one assessed along three methods: type of support, frequency, and daily time during which support i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…Verdugo et al 2017) have suggested that it is possible that the response categories need to be revised to reflect shorter increments of time or even transformed into continuous open-ended scales. One interpretation of this result may refer to the content of the items.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Verdugo et al 2017) have suggested that it is possible that the response categories need to be revised to reflect shorter increments of time or even transformed into continuous open-ended scales. One interpretation of this result may refer to the content of the items.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support the validity of the SIS-C for assessing support needs in children with ID Verdugo et al 2017;Shogren et al 2017b); however, this result has not been replicated in children with IMD. To provide evidence of validity, the first research question asked whether the measurement of support needs varies between groups.…”
Section: Objectives Of the Present Studymentioning
confidence: 95%
See 2 more Smart Citations
“…However, given that in the SIS and SIS‐C each item is rated according to three measurement methods (i.e., type, frequency and daily support time), recent studies on this topic have analysed the relative contributions of the support needs construct and the method factors in the observed support needs in adults and children with intellectual disability. These studies have shown the influence of the method factors that should not be neglected when studying the support needs construct in children and adults with intellectual disability (Seo, Shogren, Little, Thompson, & Wehmeyer, ; Verdugo, Arias, & Guillén, ).…”
Section: Methodsmentioning
confidence: 99%